(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This scientific article explores various effective methods for organizing English language lessons to enhance learning outcomes among students. By integrating innovative pedagogical approaches, technology, and interactive activities, educators can create engaging and dynamic learning environments that cater to the diverse needs of learners. This article discusses the importance of lesson planning, student engagement, differentiated instruction, and the use of technology in modern language education. By implementing these strategies, teachers can promote language acquisition, fluency, and proficiency in English among students.